Higher β-HCG concentrations and higher birthweights ensue from single vitrified embryo transfers - Keane, Kevin N; Mustafa, Kamarul Bahyah; Hinchliffe, Peter; Conceicao, Jason; Yovich, John L (Elsevier Ltd, 2016)
To examine the effect of cryopreservation on developmental potential of human embryos, this study compared quantitative β-HCG concentrations at pregnancy test after IVF-fresh embryo transfer (IVF-ET) with those arising after frozen embryo transfer (FET). It also tracked outcomes of singleton pregnancies resulting from single-embryo transfers that resulted in singleton live births (n = 869; with 417 derived from IVF-ET and 452 from FET). The initial serum β-HCG concentration indicating successful implantation was measured along with the birthweight of the ensuing infants. With testing at equivalent luteal phase lengths, the median pregnancy test β-HCG was significantly higher following FET compared with fresh IVF-ET (844.5 IU/l versus 369 IU/l; P < 0.001). Despite no significant difference in the average period of gestation (38 weeks 5 days for both groups), the mean birthweight of infants born following FET was significantly heavier by 161 g (3370 g versus 3209 g; P < 0.001). Furthermore, more infants exceeded 4000 g (P < 0.001) for FET although there was no significant difference for the macrosomic category (≥4500 g). We concluded that FET programme embryos lead to infants with equivalent (if not better) developmental potential compared with IVF-ET, demonstrated by higher pregnancy β-HCG concentrations and ensuing birthweights.